(untitled) (Medico Legal Update, 2020)
Background: Number of person suffering from some kind of illness is increasing day by day. In addition to the individuals suffering from various disease, person with medico-legal injuries or complaints are also admitted in the hospital. A hospital is a place where a patient gets required treatment, undergoes various investigations, procedures and medico-legal formalities when required. In a tertiary care hospital, Emergency Medical Officer is the first doctor to attend the patient. In any case first and foremost duty of a doctor is to save the life of patient. After providing the first aid and following the treatment protocol another duty is to do all medico-legal formalities like issuing Medico-legal reports and sending police information etc in a police case. A medico-legal case is a case where a patient has some assault injuries or having some complaint where a doctor thinks that some kind of information to police is required in the case. Aims and Objectives: To prepare and evaluate complete demographic profile of medico-legal cases admitted at our tertiary care hospital. Materials and Method: A one and half year retrospective study was conducted in department of Forensic Medicine at G.G.S. Medical College, Faridkot. This study was conducted on cases that came during the period under study i.e. from 1st January 2017 to 30th June 2018. Results: A total of 1850 medico-legal cases got registered in the emergency during the period under study. Out of these, medico-legal reports were prepared in 1510 cases. Majority of cases in which MLR was issued were of assault followed by road traffic accident. Males dominated the females and commonest age group affected was 21-30 years in our study. Majority of victims got admitted in Surgery department followed by Orthopedics and Neurosurgery department. Most victims came during period from 8PM to 8AM. Maximum number of cases reported in months of summers than winters. Most of the victims were of rural background.